Carbapenem resistance and Acinetobacter baumannii in Senegal: the paradigm of a common phenomenon in natural reservoirs. - Marie Kempf (Public Library of Science (PLoS), 2012)
Incidence of carbapenem-resistant Acinetobacter baumannii is rising in several parts of the world. In Africa, data concerning this species and its resistance to carbapenems are limited. The objective of the present study was to identify the presence of A. baumannii carbapenem-resistant encoding genes in natural reservoirs in Senegal, where antibiotic pressure is believed to be low. From October 2010 to January 2011, 354 human head lice, 717 human fecal samples and 118 animal fecal samples were screened for the presence of A. baumannii by real time PCR targeting bla(OXA51-like) gene. For all samples positive for A. baumannii, the carbapenemase-hydrolysing oxacillinases bla(OXA23-like) and bla(OXA24-like) were searched for and sequenced, and the isolates harbouring an oxacillinase were genotyped using PCR amplification and sequencing of recA gene. The presence of A. baumannii was detected in 4.0% of the head lice, in 5.4% of the human stool samples and in 5.1% of the animal stool samples tested. No bla(OXA24) gene was detected but six fecal samples and three lice were positive for bla(OXA23-like) gene. The bla(OXA23-like) gene isolated in lice was likely a new oxacillinase sequence. Finally, the A. baumannii detected in stools were all of recA genotype 3 and those detected in lice, of recA genotype 4. This study shows for the first time a reservoir of bla(OXA23-like)-positive gene in human head lice and stool samples in Senegal.